Using the Method of Mathematical Planning of the Experiment in the Development of an Optimal Technology for Obtaining Dry Extract from the Chological Collection #x201C;Triflos#x201D; (Global Journal of Medical Research, 2022)
Research is carried out on the development of technology for the dry extract of the choleretic collection "Triflos" by the method of mathematical planning of the experiment. In this case, the method of a four-factor experimental plan based on a 5x5 Greek-Latin square is used. The use of short-term ultrasonic exposure to intensify the extraction of target groups of biologically active substances is scientifically substantiated. The proposed technology is tested in industrial conditions. The dry extract yield was 21%.glaucoma. Alternative treatment with Tafluprost contributes to savings in the overall treatment procedure. Therefore, we recommend adding Tafluprost to the list of essential medicines.
Keywords: choleretic collection